Pathogenesis of Celiac Disease and Other Gluten Related Disorders in Wheat and Strategies for Mitigating Them - Sharma, Natasha; Bhatia, Simran; Chunduri, Venkatesh; Kaur, Satveer; Sharma, Saloni; Kapoor, Payal; Kumari, Anita; Garg, Monika (Frontiers in Nutrition, 2020)
Wheat is a major cereal crop providing energy and nutrients to the billions of people around the world. Gluten is a structural protein in wheat, that is necessary for its dough making properties, but it is responsible for imparting certain intolerances among some individuals, which are part of this review. Most important among these intolerances is celiac disease, that is gluten triggered T-cell mediated autoimmune enteropathy and results in villous atrophy, inflammation and damage to intestinal lining in genetically liable individuals containing human leukocyte antigen DQ2/DQ8 molecules on antigen presenting cells. Celiac disease occurs due to presence of celiac disease eliciting epitopes in gluten, particularly highly immunogenic alpha-gliadins. Another gluten related disorder is non-celiac gluten-sensitivity in which innate immune-response occurs in patients along with gastrointestinal and non-gastrointestinal symptoms, that disappear upon removal of gluten from the diet. In wheat allergy, either IgE or non-IgE mediated immune response occurs in individuals after inhalation or ingestion of wheat. Following a life-long gluten-free diet by celiac disease and non-celiac gluten-sensitivity patients is very challenging as none of wheat cultivar or related species stands safe for consumption. Hence, different molecular biology, genetic engineering, breeding, microbial, enzymatic and chemical strategies have been worked upon to reduce the celiac disease epitopes and the gluten content in wheat. Currently, only 8.4% of total population is affected by wheat-related issues, while rest of population remains safe and should not remove wheat from the diet, based on false media coverage.